The importance of quantitative research in language testing and assessment: in the context of social works - Rashid, Md. Harun; Sipahi, Esra (Linguistics and Culture Review, 2021)
These studies, in multiple fields, use many statistical analysis techniques and practices for these current studies. Some of these researchers like to be attributed to quantitative studies. Investigators are therefore intensely sharply divided, and they start competing to point out the advantages of their very own preferred techniques and technologies. However, both techniques and technologies possess pros and cons for all research teams. The objectives of this research are to know the advantages and disadvantages of using statistical research methodology for language measurement and evaluation. Focusing on ethical considerations, this study also found some strong points in the use of grounded theory for language assessment and research testing, such as the generation of more in-depth insights into the design, management, and interpretation of assessment and testing; and the exploration of behaviour, perceptions, feelings, and ability to understand of test subjects. A few other weak points are, for instance, smaller sample sizes and time-consuming quantitative research methods. However, on the other hand, they involve a large sample size and therefore do not necessitate a sufficiently long time to conduct.